Soil and water characteristics and growth of Penaeus monodon fed with formulated feed in experimental tanks - Gupta, B P; Krishnani, K K; Joseph, K O; Muralidhar, M; Ali, S A; Gopal, C (Indian Journal of Fisheries, 2011)
The changes in soil and water characteristics were studied in circular cementtanks stocked with three size groups of Penaeus monodon and fed with threegrades of formulated feeds. The water quality parameters such as turbidity(3-16NTU), ammonia(0.002-0.202 mg/1), nitrite(0.002-0.05 mg/1) and nitrate(0.002-0.046 mg/1) and that of soil such as organic carbon(0.15-0.39%), total nitrogen(0.014-0.059%) and redox potential(-40 to -190 mV) were higher in all sizegroup shrimps than the control group. The levels of ammonia, nitrite and nitratein water were high during second and third week and the organic carbon and totalN in soil were high after sixth week. All these parameters were higher withfinisher feed treatment followed by grower feed treatment. The study clearlyshows that there is a sharp increase in ammonia in the water after two weeks dueto excretion by shrimps which later effectively gets converted into nitrite andnitrate by nitrogen converting bacteria. The rise in organic carbon and total nitrogensuggests the active role of bacteria in soil water interface. The steady increasein the redox potential underlines the increasing load of organic substancesdue to uneaten feed and faecal accumulation. Growth and FOR in all the threegroups showed progressive trend which were comparable to the results obtainedin other studies.